Flouting Maxims by The Main Character in Money Monster Film - Richie Alvino (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study aims to analyze the flouting maxims contained in the Money Monster film. This study uses the qualitative method, and the unit of analysis is the utterances in the Money Monster film script. The writer is using Cutting and Fordyce's (2020) theory of flouting maxims. Flouting maxims can be divided into four categories: flouting the maxim of quantity, flouting the maxim of quality, flouting the maxim of relation, and flouting the maxim of manner. The results of this study indicate that there are all four types of flouting maxims found in the film. The total data is 11 of the flouting maxims; all of the flouting maxims are flouted by the main character in the film. Flouting maxims of quantity are flouted one-time, flouting maxims of quality are flouted two times, flouting maxims of relation are flouted five times, and flouting maxims of manner are flouted three times. The least flouted is the flouting maxim of quantity; it is only flouted once. The flouting maxim that appears the most is the flouting maxim of relation, which is flouted four times in the conversation.